2021
DOI: 10.1371/journal.pone.0246438
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA in spent culture medium effectively reflects the chromosomal status of embryos following culturing beyond implantation compared to trophectoderm biopsy

Abstract: This prospective study evaluated the accuracy of non-invasive preimplantation genetic testing for aneuploidy (niPGT-A) using cell-free DNA in spent culture medium, as well as that of preimplantation genetic testing for aneuploidy (PGT-A) using trophectoderm (TE) biopsy after culturing beyond implantation. Twenty frozen blastocysts donated by 12 patients who underwent IVF at our institution were investigated. Of these, 10 were frozen on day 5 and 10 on day 6. Spent culture medium and TE cells were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Therefore, the development of a new technology that could replace or complement the results of analysis performed using PGT-A, such as using cfDNA present in the culture supernatant, [14][15][16] is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the development of a new technology that could replace or complement the results of analysis performed using PGT-A, such as using cfDNA present in the culture supernatant, [14][15][16] is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Using the current PGT‐A method, it is difficult to accurately determine the actual chromosomal status of the whole embryo. Therefore, the development of a new technology that could replace or complement the results of analysis performed using PGT‐A, such as using cfDNA present in the culture supernatant, 14 , 15 , 16 is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we cannot identify mosaic embryos accurately because they show DNA heterogenicity, leading to a false genetic diagnosis (35)(36)(37)(38). However, mosaic embryos can give birth to healthy babies (39,40), but the dynamic implantation decreases compared to euploid embryos (41,42). In addition, researchers have found a discrepancy between the chromosomal states of cells in trophectoderm (TE) biopsies, so these cells do not necessarily represent the whole embryo (40,43,44).…”
mentioning
confidence: 99%
“…Recent studies have shown detection of cf-DNA in biological fluids, blastocyst fluid, and spent culture medium of in vitro cultured embryos (39,40,(45)(46)(47)(48)(49)(50), opening new roads for the implementation of non-invasive procedures in assisted reproductive technology. The cf-DNA that can be detected by the embryonic developmental culture material, SCM, seems to be the best choice for non-invasive PGT (ni-PGT).…”
mentioning
confidence: 99%